2018
DOI: 10.7759/cureus.2563
|View full text |Cite
|
Sign up to set email alerts
|

What Makes for Good Anesthesia Teaching by Faculty in the Operating Room? The Perspective of Anesthesiology Residents

Abstract: BackgroundTeaching during patient care is an important competency for faculty. Little is known about anesthesiology resident preferences for teaching by anesthesiology faculty in the operating room (OR). If the behaviors and characteristics of anesthesia teaching in the OR that are most valued by residents were identified, faculty could incorporate that best practice to teach residents during OR cases. The objective of this phenomenological study was to interview anesthesiology residents to determine what they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Seventy-one studies that defined the skills and behaviours of excellent clinician teachers for general feedback to faculty, or to inform FD programs were identified during our screening process. 51,[117][118][119][120][121][122][123][124] Our analysis demonstrated that there is a lack of evidence concerning the key perceived attributes of excellent clinician teachers that underpin recognition and reward decisions, with no new articles published on the topic in over a decade. 77 The lack of publications that define and clearly delineate what constitutes excellence in clinical teaching for recognition and reward decisions is a clear barrier to understanding this phenomenon and its potential effects on the clinical teaching workforce.…”
Section: Cognitive and Non-cognitive Attributes Of Excellent Clinicia...mentioning
confidence: 99%
“…Seventy-one studies that defined the skills and behaviours of excellent clinician teachers for general feedback to faculty, or to inform FD programs were identified during our screening process. 51,[117][118][119][120][121][122][123][124] Our analysis demonstrated that there is a lack of evidence concerning the key perceived attributes of excellent clinician teachers that underpin recognition and reward decisions, with no new articles published on the topic in over a decade. 77 The lack of publications that define and clearly delineate what constitutes excellence in clinical teaching for recognition and reward decisions is a clear barrier to understanding this phenomenon and its potential effects on the clinical teaching workforce.…”
Section: Cognitive and Non-cognitive Attributes Of Excellent Clinicia...mentioning
confidence: 99%
“…Wakatsuki et al interviewed anesthesia residents to find out what their most effective attending teachers in the operating room were doing that others were not and found that fostering autonomy was one of the nine key behaviors these faculty exhibited [10]. This behavior and the other effective teaching behaviors identified in this study fit within the cognitive apprenticeship framework of learning, which includes teaching methods such as scaffolding, modeling, articulation, reflection, and exploration [11].…”
Section: Cognitive Apprenticeship Frameworkmentioning
confidence: 68%
“…We highlight that although low stakes procedurally, USPIV placement is a skill that requires significant experience to master and that we will be giving real-time feedback and instruction at the bedside to support them through a successful IV insertion to encourage an open dialogue between the learner and instructor. This establishes the learning environment and psychologic safety, which has been described in many educational settings to beneficial for learning ( 22 24 ). Specifically, the psychological safety that we aim to establish emphasizes the trainee’s ability to fully engage in the learning experience without a sense of needing to preserve their image or be concerned about judgement.…”
Section: What Is the Approach?mentioning
confidence: 88%